Use of Mechanistic Models to Investigate Fatigue Performance of Asphalt Mixtures: Effects of Asphalt Mix Design Targets and Compaction. Issue 1 (January 2015) - Lee, Jong-Sub; Gibson, Nelson; Kim, Y. Richard
Effects of design air void contents, design voids in mineral aggregate (VMA), and in-place air voids on the fatigue performance of asphalt mixtures were investigated with mechanistic analyses based on the viscoelastic continuum damage (VECD) analyses and the mechanistic–empirical pavement analysis using the AASHTOWare Pavement ME Design program. The VECD analyses included the simplified viscoelastic continuum damage model at the material level and two structural models: ( a ) layered viscoelastic analysis and ( b ) layered viscoelastic pavement analysis for critical distresses. The mix design of a 2013 accelerated loading facility test lane was selected to develop the volumetric mix designs with the design air voids of 3%, 4%, and 5%, design VMAs of 13%, 14%, and 15%, and in-place air void contents of 5%, 7%, and 9% with the Bailey method. Dynamic modulus and direct tension cyclic fatigue tests were performed in accordance with the AASHTO TP 107 procedure. The test results showed that the linear viscoelastic property was affected by the design VMA, design air void content, and in-place air void content in order of sensitivity. Also, the damage states at failure determined from the damage characteristic curves and the mechanistic fatigue predictions had consistent trends as observed for the design VMA, in-place air void, and design air void content in rank of sensitivity. Finally, the design VMA, in-place air void, and design air void parameters were found to be sensitive in the mechanistic analyses, whereas the parameter that was most sensitive in the pavement mechanistic–empirical analysis was the in-place air void content.